Nursing of a pediatric patient with immune dysregulation, polyendocrinopathy, enteropathy, X-linked syndrome (1例罕见IPEX综合征患儿的护理) - ZHU Huiyun (朱慧云); WANG Suling (王苏玲) (中西医结合护理)
Immune dysregulation, polyendocrinopathy, enteropathy, X-linked (IPEX) syndrome is a rare, fatal autoimmune disorder caused by mutations in the FOXP3 gene leading to the disruption of signaling pathways involved in regulatory T-lymphocyte function. This paper reviewed the clinical data of an IPEX child with respiratory and gastrointestinal symptoms as main symptoms, and summarized treatment and nursing experience. During the treatment, comprehensive interventions such as airway management, individualized nutrition support, medication care, psychological care of primary caregivers, skin care and healthcare education were carried out to reduce the incidence of complications and improve the recovery of the patient. (X-连锁多内分泌腺病肠病伴免疫失调综合征(IPEX)在临床上极为罕见。本文回顾医院收治1例以免疫系统低下引起的呼吸系统症状以及消化系统症状为主的IPEX患儿的临床资料, 总结护理经验。治疗期间, 给予患儿呼吸道管理和个体化营养干预, 加强用药护理、主要照顾者心理护理、皮肤护理和健康教育, 降低并发症发生风险, 促进患儿康复。)